The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Rainfall and temperature influence effectiveness of on-site sanitation intervention against E. coli contamination in Bangladeshi households - Caitlin G. Niven; Mahfuza Islam; Anna Nguyen; Andrew Mertens; Amy J. Pickering; Laura H. Kwong; Mahfuja Alam; Debashis Sen; Sharmin Islam; Mahbubur Rahman; Leanne Unicomb; Alan E. Hubbard; et al. (International Journal of Hygiene and Environmental Health, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Green synthesis of silver nanoparticles from Passiflora edulis: comparison with conventional methods and biomedical applications - F. Mutlag; H. Elaibi; E. Halvaci; F. Sen (International Journal of Environmental Science and Technology, 2026)

Development of environmentally friendly lightweight aerogel composites as sustainable building materials: high insulation performance and application potential - M. P. Balci; R. Bayat; C. Karakurt; F. Sen (International Journal of Environmental Science and Technology, 2025)
In this study, inexpensive and environmentally friendly aerogel insulation composites were synthesized using diatomite. During the synthesis, raw diatomite, polyvinyl alcohol (PVA) and carboxymethyl cellulose (CMS) were used as binders and only water was used as solvent. The freeze-drying method enables the formation of an aerogel structure with low density (0.114 g/cm 3 ) and high porosity (91.50%), making it suitable for applications such as thermal insulation. The final LWA aerogel has a very low thermal conductivity of 0.041 W/(m.K). The synthesized aerogels were combined with ready-made plasterboard to obtain a lightweight aerogel composite. A test box with plasterboard walls was prepared with the obtained LWA composite and the internal temperatures and surface temperatures were measured. Comparative measurements with the test box without LWA composite showed a temperature difference of approximately 7 °C. The use of diatomite without any pre-treatment makes aerogel an environmentally friendly and cost-effective material. It is thought that such innovative materials will contribute to sustainability in industrial applications. In conclusion, the findings of the study reveal that diatomite-based lightweight aerogels offer new opportunities as building materials.

Associations between floor material and E. coli contamination in rural Bangladeshi households - Sumaiya Tazin; Mahfuza Islam; Amy J. Pickering; Laura H. Kwong; Andrew Mertens; Caitlin Niven; Benjamin F. Arnold; Alan E. Hubbard; Mahfuja Alam; Debashis Sen; Sharmin Islam; Mahbubur Rahman; et al. (International Journal of Hygiene and Environmental Health, 2025)

Role of Trametes multicolor in green nanotechnology based antioxidant, antimicrobial, lipid peroxidation inhibition from fungi to nanoparticles - Y. Kocak; E. Okumus; I. Meydan; H. Seckin; M. Bekmezci; F. Sen (International Journal of Environmental Science and Technology, 2025)

The Impact of Liraglutide, a GLP-1 Receptor Agonist, on High Glucose-Induced Inflammation, Apoptosis, Oxidative Stress, and NLRP3 Signaling - Mustafa Gokce; Dilek Ozturk Civelek; Aylin Vidin Sen; Eray Metin Guler; Erkan Civelek; Birsel Sonmez Uydes Dogan; F. Ilkay Alp Yildirim (Cell Biochemistry and Biophysics, 2025)

Evaluation of antioxidant, antibacterial and thermal stability properties of silver nanoparticles synthesised with Infundibulicybe gibba extract - I. Meydan; H. Seckin; Y. Kocak; E. Okumus; M. Bekmezci; F. Sen (International Journal of Environmental Science and Technology, 2025)

Characterisation, antibacterial and antioxidant effects of mountain tea (Sideritis L.) mediated silver nanoparticles in preventing DNA damage - T. Gur; M. Bekmezci; I. Meydan; H. Seckin; F. Sen (International Journal of Environmental Science and Technology, 2025)

Development of thermoelectric Ca3Co4O9 crystals for thermo-photovoltaic hybrid energy conversion - N. D. Coşkun; V. Uz; H. Gaşan; F. Sen (International Journal of Environmental Science and Technology, 2025)

Levulinic acid-based deep eutectic solvent and n-heptane for efficient oil extraction process from rubber seed - Mohammed Abobakr Al-Maari; Hanee F. Hizaddin; Adeeb Hayyan; Khalid M. Abed; Wan Jefrey Basirun; Yousef Mohammed Alanazi; Jehad Saleh; Mohd Ali Hashim; Bhaskar Sen Gupta (Food and Bioproducts Processing, 2025)

Eco-friendly production of platinum nanoparticles: physicochemical properties, evaluation of biological and catalytic activities - Y. Kocak; A. Aygun; E. E. Altuner; S. Ozdemir; S. Gonca; D. Berikten; R. N. E. Tiri; F. Sen (International Journal of Environmental Science and Technology, 2024)

Acetate based CaMnO3 thermoelectric material synthesis: effects on efficiency, phase formation, and microstructural change - F. Çelik; N. D. Coşkun; V. Uz; H. S. Aydoğu; İ. Işık; R. Bayat; F. Sen (International Journal of Environmental Science and Technology, 2023)

Constraining the sources and cycling of dissolved inorganic carbon in an alpine river, eastern Qinghai-Tibet Plateau - Wanfa Wang; Jun Zhong; Si-Liang Li; F. Ulloa-Cedamanos; Sen Xu; Sainan Chen; Manting Lai; Sheng Xu (Science of The Total Environment, 2023)

Bioaccumulation, resistance, and remediation of Mn(II) and Cu(II) and their impacts on antioxidant enzymes of Anoxybacillus flavithermus - S. Özdemir; Z. Turkan; E. Kılınc; E. E. Altuner; F. Sen (International Journal of Environmental Science and Technology, 2023)

Investigation of energy efficiency of heating systems in power plant boilers for different conditions with CFD analysis - H. D. Yildizay; Ö. Aydin; Y. Erhan Böke; I. Y. Uralcan; F. Sen (International Journal of Environmental Science and Technology, 2023)

High-performance aggregate production by sintering terra rossa containing pyrophyllite and colloidal calcite - M. U. Toprak; C. Karakurt; Y. Kibici; V. Uz; F. Sen; F. Bilen (International Journal of Environmental Science and Technology, 2023)

Determination of the sintering behaviour of apatite using multiple characterization techniques - N. D. Coşkun; I. Işık; V. Uz; R. Gören; P. B. Çetinkaya; E. Işık; F. Sen (International Journal of Environmental Science and Technology, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Investigation of mycosynthesized silver nanoparticles by the mushroom Pleurotus eryngii in biomedical applications - Y. Kocak; I. Meydan; T. Gur Karahan; F. Sen (International Journal of Environmental Science and Technology, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Assessment of heavy metal contamination and its sources in urban soils of district Hyderabad, Pakistan using GIS and multivariate analysis - R. K. Bux; S. I. Haider; M. Batool; A. R. Solangi; Z. Shah; H. Karimi-Maleh; F. Sen (International Journal of Environmental Science and Technology, 2022)

Assessing male gelada chest patches: color measurement and physiological mechanisms - Patricia M. DeLacey; Rachel F. Perlman; Sharmi Sen; India Schneider-Crease; Kenneth L. Chiou; Alemayehu Lemma; Ferehiwot Ayele; James P. Higham; Amy Lu; Noah Snyder-Mackler; Jacinta C. Beehner; Thore J. Bergman (Mammalian Biology, 2022)

Investigation of the antibacterial properties of silver nanoparticles synthesized using Abelmoschus esculentus extract and their ceramic applications - F. Elmusa; A. Aygun; F. Gulbagca; A. Seyrankaya; F. Göl; C. Yenikaya; F. Sen (International Journal of Environmental Science and Technology, 2021)

Are spliced ncRNA host genes distinct classes of lncRNAs? - Rituparno Sen; Jörg Fallmann; Maria Emília M. T. Walter; Peter F. Stadler (Theory in Biosciences, 2020)
Many small nucleolar RNAs and many of the hairpin precursors of miRNAs are processed from long non-protein-coding host genes. In contrast to their highly conserved and heavily structured payload, the host genes feature poorly conserved sequences. Nevertheless, there is mounting evidence that the host genes have biological functions beyond their primary task of carrying a ncRNA as payload. So far, no connections between the function of the host genes and the function of their payloads have been reported. Here we investigate whether there is evidence for an association of host gene function or mechanisms with the type of payload. To assess this hypothesis we test whether the miRNA host genes (MIRHGs), snoRNA host genes (SNHGs), and other lncRNA host genes can be distinguished based on sequence and/or structure features unrelated to their payload. A positive answer would imply a functional and mechanistic correlation between host genes and their payload, provided the classification does not depend on the presence and type of the payload. A negative answer would indicate that to the extent that secondary functions are acquired, they are not strongly constrained by the prior, primary function of the payload. We find that the three classes can be distinguished reliably when the classifier is allowed to extract features from the payloads. They become virtually indistinguishable, however, as soon as only sequence and structure of parts of the host gene distal from the snoRNAs or miRNA payload is used for classification. This indicates that the functions of MIRHGs and SNHGs are largely independent of the functions of their payloads. Furthermore, there is no evidence that the MIRHGs and SNHGs form coherent classes of long non-coding RNAs distinguished by features other than their payloads.

Biogenic Silica Composition and Storage in the Yellow River Delta Wetland with Implications for the Carbon Preservation - Jun Liu; Zhaoliang Song; Jianbu Wang; Alexander F. Bouwman; Menglu Li; Sen Liu; Lei Cao; Jiaye Zang; Xiangbin Ran (Wetlands, 2020)

Preservation of Tilapia ( Oreochromis aureus ) Fillet by Isochoric (Constant Volume) Freezing - Cristina Bilbao-Sainz; Amanda J. G. Sinrod; Tina Williams; Delilah Wood; Bor-Sen Chiou; David F. Bridges; Vivian C. H. Wu; Chenang Lyu; Boris Rubinsky; Tara McHugh (Journal of Aquatic Food Product Technology, 2020)

Field cage assessment of feeding damage by Halyomorpha halys on kiwifruit orchards in China - Ju-Hong Chen; Gonzalo A. Avila; Feng Zhang; Lindy F. Guo; Manoharie Sandanayaka; Qian-Qian Mi; Shu-Sen Shi; Jin-Ping Zhang (Journal of Pest Science, 2020)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Cerebellar-Stimulation Evoked Prefrontal Electrical Synchrony Is Modulated by GABA - Xiaoming Du; Laura M. Rowland; Ann Summerfelt; Fow-Sen Choa; George F. Wittenberg; Krista Wisner; Andrea Wijtenburg; Joshua Chiappelli; Peter Kochunov; L. Elliot Hong (The Cerebellum, 2018)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Molecular cloning and characterization of gonadotropin subunits (GTHα, FSHβ and LHβ) and their regulation by hCG and GnRHa in Japanese sea bass (Lateolabrax japonicas) in vivo - Mei L. Chi; Meng Ni; Ji F. Li; Feng He; Kun Qian; Pei Zhang; Sen H. Chai; Hai S. Wen (Fish Physiology and Biochemistry, 2015)

Assessment of the CMIP5 global climate model simulations of the western tropical Pacific climate system and comparison to CMIP3 - Michael R. Grose; Jaclyn N. Brown; Sugata Narsey; Josephine R. Brown; Bradley F. Murphy; Clothilde Langlais; Alex Sen Gupta; Aurel F. Moise; Damien B. Irving (International Journal of Climatology, 2014)
A set of 27 global climate models from the Coupled Model Inter‐comparison Project Phase 5 ( CMIP5 ) ensemble are assessed for their performance for the purpose of making future climate projection studies in the western tropical Pacific and differences to Coupled Model Inter‐comparison Project Phase 3 ( CMIP3 ) are assessed. The CMIP5 models show some improvements upon CMIP3 in the simulation of the climate in the western tropical Pacific in the late 20th century. There are fewer CMIP5 models with very poor skill scores than in CMIP3 for some measures and a small group of the well‐performing models in CMIP5 have lower biases than in an equivalent group from CMIP3 . These best‐performing models could be particularly informative for studying certain climate sensitivities and feedbacks in the region. There is evidence to reject one model as unsuitable for making regional climate projections in the region, and another two models unsuitable for analysis of the South Pacific Convergence Zone (SPCZ). However, while there have been improvements, many of the systematic model biases in the mean climate in CMIP3 are also present in the CMIP5 models. They are primarily related to the shape of the transition between the Indo‐Pacific warm pool and equatorial cold tongue, and the associated biases in the position and orientation of the SPCZ and Inter‐Tropical Convergence Zone, as well as in the spatial pattern, variability and teleconnections of the West Pacific monsoon, and the simulation of El Niño Southern Oscillation. Overall, the results show that careful interpretation and consideration of biases is required when using CMIP5 outputs for generating regional climate projections for the western tropical Pacific, particularly at the country scale, just as there was with CMIP3 .

The Indo-Australian monsoon and its relationship to ENSO and IOD in reanalysis data and the CMIP3/CMIP5 simulations - Nicolas C. Jourdain; Alexander Sen Gupta; Andréa S. Taschetto; Caroline C. Ummenhofer; Aurel F. Moise; Karumuri Ashok (Climate Dynamics, 2013)

Erratum to: Screening for new sources of resistance to Clavibacter michiganensis subsp. michiganensis (Cmm) in tomato - Yusuf Sen; Feng Zhu; Henri Vandenbroucke; Jan van der Wolf; Richard G. F. Visser; A. W. van Heusden (Euphytica, 2013)

Screening for new sources of resistance to Clavibacter michiganensis subsp. michiganensis (Cmm) in tomato - Yusuf Sen; Zhu Feng; Henri Vandenbroucke; Jan van der Wolf; Richard G. F. Visser; A. W. van Heusden (Euphytica, 2013)

Characterization of soil heavy metal pools in paddy fields in Taiwan: chemical extraction and solid-solution partitioning - Paul F. Römkens; Horng-Yuh Guo; Chien-Liang Chu; Tsang-Sen Liu; Chih-Feng Chiang; Gerwin F. Koopmans (Journal of Soils and Sediments, 2009)

Hypoxia in the northern Gulf of Mexico: Does the science support the Plan to Reduce, Mitigate, and Control Hypoxia? - N. N. Rabalais; R. E. Turner; B. K Sen Gupta; D. F. Boesch; P. Chapman; M. C. Murrell (Estuaries and Coasts, 2007)

On optimization algorithms for the reservoir oil well placement problem - W. Bangerth; H. Klie; M. F. Wheeler; P. L. Stoffa; M. K. Sen (Computational Geosciences, 2006)

The Evaluation of Coagulation Profiles in Calves with Suspected Septic Shock - K. Irmak; I. Sen; R. Cöl; F. M. Birdane; H. Güzelbektes; T. Civelek; A. Yιlmaz; K. Turgut (Veterinary Research Communications, 2006)

Apoptosis and interferons: Role of interferon-stimulated genes as mediators of apoptosis - M. Chawla-Sarkar; D. J. Lindner; Y.-F. Liu; B. R. Williams; G. C. Sen; R. H. Silverman; E. C. Borden (Apoptosis, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)